“If only balls could talk…”: barriers and opportunities to participation for students with blindness and visual impairment in specialized PE - Meier, Stefan; Höger, Brigitta; Giese, Martin (Frontiers in Sports and Active Living, 2023)
Purpose: For blind and visually impaired (BVI) children of all ages, disability sport and/or regular Physical Activity (PA) are deemed beneficial, promoting physical and mental health as well as increasing wellbeing and life satisfaction. In this regard, Physical Education (PE) serves as a foundation to regular and lifelong participation in PA, mainstream and/or disability sport. Research points towards manifold participation barriers for BVI children in PE, which so far have mainly been investigated in inclusive settings and from the perspectives of sighted parents, teachers and peers. Consequently, BVI people frequently consider PE a missed opportunity for lifelong PA. As transitioning from general to special schooling deems the only alternative to continue their education, questions arise in how far and in which ways specialized schools manage to accommodate their needs in PE. To address these gaps in literature, we investigated BVI students’ perceived opportunities and barriers to participation in PE within a specialized school setting and their imaginations for possible (digital) improvements and solutions. Materials and methods: Within the framework of Inclusive and Youth Participatory Action Research, we adopted the Mosaic Approach to investigate a sample of 19 students aged 14-20 at lower and upper secondary level in specialized schools in Austria. Data material included audio-recordings of interviews, student-guided school tours, photographs of significant places and objects and field protocols. The analysis was conducted with Interpretative Phenomenological Analysis. Results and conclusion: Through the analysis, we identified three themes. The data material firstly revealed the complex intricacies of how PE teachers can act as facilitators and gatekeepers to autonomous PA. Secondly, material norms function not only as barriers to participation even in a specialized school setting, but also constitute the basis for social hierarchies between students with various degrees of visual impairment. Thirdly, students imagined manifold digital solutions to enhance participation derived from their perceived barriers. The findings contribute to amplifying BVI individuals’ voices and provide revealing insights in how participation in PA is enabled and prohibited for BVI students, which can not only help to improve specialized but also inclusive settings.